STUDENTS’ RESPONSES TOWARD COGNITIVE ASSESSMENT BASED ON HIGHER ORDER THINKING SKILLS (HOTS) ASSISTED BY THE QUIZIZZ APPLICATION - Aseptiana Parmawati; Siti Ruqoyyah (IKIP Siliwangi, 2023)
The development of the world of education is rapidly, therefore every student is required to have the ability to think critically and creatively. So to be able to achieve this ability requires innovation both in the use of learning media interactive and HOTS-based cognitive assessment instruments. In the field of education instruments are used to measure learning achievement of students, the success of the learning process and the development of results study. Quizizz is a game-based educational app that brings multiplayer activities to the classroom and make learning in the classroom more fun and more interactive. Quizizz application can use by the teacher in teaching and learning process. The purpose of this research was to find out the students’ responses toward cognitive assessment based on higher order thinking skills (hots) assisted by the quizizz application. Case study was used in this research.Data was collected by conducting observation and giving questionnaire. Based on the result, most of students have positive statements toward quizizz application during the assessment process. Almost students experienced fun and interesting with the quizizz as learning tool of assessment. Keywords: Students’ Response; Assessment; HOTS; Quizizz